Controlador lógico programável alternativo de livre acesso baseado em um microcontrolador PIC - Queiroz, Willian Felipe Dreher (2022)
The programmable logic controller appeared in the late 60’s to replace the relay logic, bringing the ability to reprogram the system’s operating logic, taking up less space and thus were widely accepted by the industry. With the evolution of eletronics, They stopped just replacing relay logic and added new control functions such as temporization, arithmetic operations, data acquisition, communication with other devices, amongst others functions. But due to this evolution, the programmable logic controller has become an expensive device, which makes it viable for controlling large automation systems, but for small applications, it becomes an expensive and unfeasible alternative. In this context, this work aims to develop a programmable logic controller based on PIC microcontrollers, as a lowcost alternative, aiming its application in small automation systems. This device brings together the main features expected in a programmable logic controller, such a digital input and outputs, analog inputs and outputs and communication interface with other devices. Electrical circuits and printed circuit boards were developed, followed by the construction of the device and the evaluation of its performance. This Project has resulted in an alternative programmable logical controller divided in modules, costing approximately 290brazilianreais to produce a unit. From the performance tests, it has proven the capacity of the device to detect signals sent by industrial sensors PNP, trigger charges of AC or DC current, measure and generate analog voltage signals with amplitude between 0 and 10V, in addition to communicating with other devices through RS232 and RS485 standards.